2013
DOI: 10.2298/pim1308197a
|View full text |Cite
|
Sign up to set email alerts
|

Duality principle and special Osserman manifolds

Abstract: We investigate the connection between the duality principle and the Osserman condition in a pseudo-Riemannian setting. We prove that a connected pointwise two-leaves Osserman manifold of dimension n 5 is globally Osserman and investigate the relation between the special Osserman condition and the two-leaves Osserman one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The duality principle for Osserman curvature tensor works for every known example, however we failed to prove it in general. In our previous work [1,2,4] we gave the affirmative answer only for the conditions of small index (ν ≤ 1) or low dimension (n ≤ 4). In this text, we restrict our attention to small numbers of eigenvalues of the reduced Jacobi operator.…”
Section: Definition 1 (Duality Principle)mentioning
confidence: 83%
See 2 more Smart Citations
“…The duality principle for Osserman curvature tensor works for every known example, however we failed to prove it in general. In our previous work [1,2,4] we gave the affirmative answer only for the conditions of small index (ν ≤ 1) or low dimension (n ≤ 4). In this text, we restrict our attention to small numbers of eigenvalues of the reduced Jacobi operator.…”
Section: Definition 1 (Duality Principle)mentioning
confidence: 83%
“…This is the reason why we devote our attention to the first nontrivial case, the diagonalizable Osserman curvature tensor whose reduced Jacobi operator has two distinct eigenvalues, and we call it a two-leaves Osserman (Definition 3). The duality principle holds for n ≤ 4 [1][2][3][4], but every connected pointwise two-leaves Osserman manifold is a globally Osserman for n > 4 [2,9]. This is why we put the problem into a pure algebraic concept with an algebraic Osserman curvature tensor instead of working with an Osserman manifold and associated tangent bundles.…”
Section: Definition 1 (Duality Principle)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] this equivalence was extended to the Lorentzian signature, and it was also shown that the duality principle holds for algebraic curvature tensors R with the Clifford structure (all such R are Osserman). Further results on the duality principle can be found in [1,2].…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, we have the following partial results. Any four-dimensional Osserman R is Jacobi-dual, see Andrejić [1]. Any Lorentzian totally Jacobidual R has constant sectional curvature, see Andrejić and Rakić [4].…”
Section: Introductionmentioning
confidence: 99%